1974
DOI: 10.1002/cber.19741070106
|View full text |Cite
|
Sign up to set email alerts
|

Rotationsbarriere in 1,2‐Dienen; Resonanzenergie des Allyl‐Radikals

Abstract: Die Rotationsbarriere der C--C-Bindungen im 1,3-Dimethyl-(la) und 1,3-Di-tert-butylallen (1 b) wurde aus den in der Gasphase crrnittelten Racemisierungsgeschwindigkeiten zu 46

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
5

Year Published

1975
1975
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 20 publications
2
31
1
5
Order By: Relevance
“…This value is much higher than the 46.2 and 46.9 kcal mol -I barriers for the thermal racemization of optically active 2,3-pentadiene and 1,3-di-tert-butylallene, respectively, a process for which planar allenes were suggested transition state species [83]. Consistent with this result is a calculated [18] barrier to racemization of S0.1 kcal tool -I (Section II.C) corresponding to a bent, planar allene singlet diradical as the transition state.…”
Section: Planar Allenesmentioning
confidence: 83%
“…This value is much higher than the 46.2 and 46.9 kcal mol -I barriers for the thermal racemization of optically active 2,3-pentadiene and 1,3-di-tert-butylallene, respectively, a process for which planar allenes were suggested transition state species [83]. Consistent with this result is a calculated [18] barrier to racemization of S0.1 kcal tool -I (Section II.C) corresponding to a bent, planar allene singlet diradical as the transition state.…”
Section: Planar Allenesmentioning
confidence: 83%
“…20,21 When the resulting 6a 1 orbital is occupied, the energies of the C 2V structures can be lower than that of the linear structures.…”
Section: Table 4: Absolute Energies (In Au) Number Of Imaginary Freqmentioning
confidence: 97%
“…At his best level of theory, the barrier is 45.1 kcal mol -1 , 7a,c in agreement with the experimental barriers for 1,3-dimethyl-and 1,3-di-tert-butylallene (46.2 and 46.9 kcal mol -1 , respectively). 20 Somewhat higher activation barriers (which would be expected for the unsubstituted species) were obtained by Seeger 21 (50.1 kcal mol -1 ) and by Rauk et al 15 (48.0 kcal mol -1 , MP3/6-31G**//RHF/3-21G). As Roth 20 suggested and Seeger 21 et al confirmed computationally, the TS is a planar bent C 2V symmetric species corresponding to a 1 A 2 singlet biradical.…”
Section: Introductionmentioning
confidence: 95%
“…Die Rotationsbarriere der C=C-Bindung in 1,3-Dimethylallen wurde aus der in der Gasphase ermittelten Racemisierungsgeschwindigkeit zu 46,2 kcal/mol bestimmt [19]. Unter (a und b)4) formuliert werden kann (vgl.…”
Section: Synthese Derunclassified